Optimization Design of CO2 Air Cooler - Liu Bin; Su Yun; Dong Xiaoyong; Wang Congfei; Cai Jinghui (Zhileng xuebao)
The design process of the air cooler used in refrigerated warehouse is introduced in detail and optimization algorithms are used to optimize the structure of the air cooler of CO2. Volume and the heat transfer coefficient of the heat exchanger are taken as an object function respectively, and fin-pitch, tube distance, tube rows, row numbers, diameter of heat pipe and the lengths of single pipe are selected as decision variables. However, according to the results of optimization, both the two algorithms are defect and insufficient, so the structure of the CO2 air cooler is optimized by the multi-objective optimization with the heat transfer coefficient, volume, air-side pressure drop. It shows that the multi-objective optimization is effective with the weight coefficients. The optimization results are verified by the experiments. Finally, the sensitive analysis of the structure is given based on the optimal result above.